Dinâmica nictimeral e sazonal do microfitoplâncton do estuário do rio Curuperé, Curuçá (PA) - REIS, Fernanda Nogueira dos (2020)
Diel variation of phytoplankton in the Curuperé creek estuary, located at Curuçá municipality, Pará State, Brazil, and its relationship with hydrological parameters and tidal regime during the rainy season (May 2013) and drier (less rainy) season (October 2013) is discussed. To this aim, 24-hour sampling was made at a fixed station, along the shore of the Curuperé Marine Aquaculture Station (SEPAQ-PA) during spring tides, and the samples of phytoplankton obtained with conical - cylindrical net, 20 μm opening mesh and fixed in 1% formaldehyde solution. Tidal regime followed prediction from the Department of Hydrology and Navigation of the Brazilian Navy, while other abiotic parameters (water transparency, pH, temperature and conductivity as well as local depth) were registered in situ for every sampling hour. Water samples were collected for later analysis of nutrient concentration. The patterns of composition, abundance, frequency, diversity, equitabity and richness were related to the tidal regime, and seasonal fluctuations. Despite high species richness registered, community showed a low diversity structure. The species Campylosira cymbelliformis was dominant in both seasons, limiting in this way the presence of other species in the estuary. The region has a well-defined seasonal cycle, with a significant difference between rainy and drier periods causing strikingly changes in the other physical, chemical and biological parameters monitored on the site. The patterns of species richness, diversity and evenness of the community followed the patterns of seasonal variation of the abiotic components of the system. Diel variation was also well defined for each season, flooding tides and daytime hours were the main factors that contributed to the increase of abundance, species richness, as well as community diversity and equitabity in Curuperé creek.